Unveiling the genetic variability, character association and principal component analysis for yield and yield contributing traits in brinjal (Solanum melongena) genotypes - R, KOUSALYA; S, PRANEETHA; P, IRENE VETHAMONI; V, RAVICHANDRAN; K, IYANAR; S, VARANAVASIAPPAN (The Indian Journal of Agricultural Sciences, 2024)
The experiment was conducted during rainy (kharif) and winter (rabi) seasons of 2023 and 2024 at Tamil Nadu Agricultural University, Coimbatore, Tamil Nadu to assess 45 brinjal (Solanum melongena L.) genotypes for growth and yield related parameters. The experiment was laid out in randomized block design (RBD) with three replications. The result showed high genotypic coefficient of variance (GCV) and phenotypic coefficient of variance (PCV) values for plant height, number of primary branches/plant, length of fruit and weight of fruit and yield/plant. Whereas, the traits such as days to first flowering, days to 50% flowering, fruit girth, fruit borer infestation and number of fruits/ plant exhibited medium GCV and PCV values. The registered high heritability values ranged from 94.29–99.49% and genetic advance as a percentage of the mean ranged from 19.25–70.25%. Correlation analysis on number of fruits/ plant showed positive and significant association with fruit yield/plant. Principal component analysis showed four principal components with eigen values of unity and accounted for 75.81% of total variance.